The Effectiveness of Hot Herbal Compress in Accelerate Uterine Involution and Recovery of Afterpains on the Postpartum Mothers - Karimah, Nahdiyah; Supriyana; Sumarni, Sri; Sunarto (ENDLESS: INTERNATIONAL JOURNAL OF FUTURE STUDIES, 2022)
About 55% of postpartum mothers in Banyumanik and Ungaran districts in October 2019 experienced uterine subinvolution, and 75% of them experienced afterpains. Hot Herbal Compress could stimulate myometrium contraction required for uterine involution and analgesic effect. This study aimed to prove the effectiveness of hot herbal compress in accelerating uterine involution and afterpain recovery on postpartum mothers. This research used a quasi-experimental design—the investigation from 13 December 2019 until 26 January 2020 in Semarang. The authors grouped 42 postpartum mothers equally into experimental and control groups with random cluster sampling. The experimental group received a hot herbal compress for 20 minutes. The control group received uterus massage for 10 minutes and breathing exercises for 15 minutes. Both groups received the therapy 1x/day from the 2nd-10th day of the postpartum period. The observation of uterine fundal height by metlin, lochia volume by gravimetric, and afterpains intensity by visual analogue scale before and after the intervention every day. The analysis used Repeated Measure Anova. The experimental group's uterine fundal height, lochia volume, and afterpains intensity were consistently lower than the control group. There were significant differences between the experimental and control groups on a uterine fundal height on days 1-5 and 6-8, on lochia volume on days 5-6, and on the intensity of afterpains on days 1-4 (p < 0.05). The hot herbal compress effectively decreased the uterine fundal height on a uterine fundal size on days 1-5 and 6-8, reduced lochia volume on days 5-6 and effectively decreased afterpains intensity on days 1-4 on of postpartum mothers. This study recommends that midwives provide hot herbal compress therapy for the postpartum mother to accelerate uterine involution and recovery of afterpains.